(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The art treasures of the Vatican in the Lateran Treaty ABSTRACT: Drawing inspiration from a recent initiative by the Pontiff, the contribution focuses on the peculiar juridical condition of the art treasures kept in the Vatican City, resulting from a series of provisions of the Lateran Treaty, other international conventions and recent Vatican legislation on the protection of cultural heritage. The result is a complex and articulated regulatory framework that underlines the role of the Holy See as a custodian and guarantor of one of the greatest historical and artistic heritages of humanity. SOMMARIO - 1. Un gesto ecumenico di papa Francesco - 2. L’art. 18 del Trattato lateranense - 3. L’articolato quadro normativo attuale - 4. Suggestioni e questioni emergenti - 5. I tesori d’arte del Vaticano e la loro peculiare condizione giuridica - 6. Osservazioni conclusive.